시설보호아동과 일반아동의 내외통제소재와 스트레스 대처행동 및 우울의 관계 - 한지현(Ji Hyoen Han); 이진숙(Jin Suk Lee) (Korean Journal of child studies, 2007)
Subjects were 134 institutionalized children(86 boys, 48 girls) and 218 non-institutionalized children(115 boys, 103 girls). Findings were that (1) institutionalized children showed lower internal locus of control than non-institutionalized children. (2) Institutionalized children with internal locus of control showed active coping behavior. Non-institutionalized children with internal locus of control showed active and social support seeking coping behavior, and non-institutional children with external locus of control showed aggressive coping behavior. (3) Regression analysis models showed that institutionalized girls were more depressed than boys; depressed institutionalized children were oriented to external locus of control and passive coping behavior. Depressed non-institutionalized children were oriented to external locus of control and passive, evasive coping behavior and showed lower active and social support seeking behavior.